Noun Phrase in the USS Feed Instagram Captions - Fajrhi, Nur; Maricar, Farida (IAIN KENDARI, 2025)
A noun phrase (NP) is a syntactic category that plays an important role in forming a sentence, along with a verb phrase. The form required at least one noun as the head, and may be accompanied by pre- and post-modifiers. This study aims to examine whether NP structures continue to play a vital role in shaping meaning in emerging forms of communication. This study was carried out in three stages: data collection, data analysis, and presentation of results. The data were collected through observation, while the basic technique employed was tapping. The data used is the 10 most popular USS Feed Instagram post captions during April. In the data analysis, the data were classified into NP’s categorisation based on (Quirk, Randolph; Greenbaum, Sidney; Leech, Geoffrey; Svartvik, 1985). The data were then presented both formally and informally. The result shows that out of 10 Instagram captions, a total of 310 NPs were identified, 193 basic NPs, and 117 complex NPs. The basic NPs appear in the form of a noun and its premodifier (s), while a post-modifier or both pre-modifiers and post-modifiers may accompany the complex NPs. The complex NP can sometimes be confusing because it includes too much information within one structure.